Ascensão do olhar: aproximações entre fenomenologia e literatura - Fiuza, Marina Miranda (2011)
The quest for ontology may be considered the main feature of the rational man. Many are the paths man has trailed to understand his own existence and the one of the world that surrounds him. In this work, we bring together two manifestations of the human being in its desire to self-knowledge: Phenomenology and Literature. However they belong to different fields of knowledge, both suggest the reconciliation between man and his nature by similar means, based on the rupture of the functional relationship the Western man is used to establishing with the world and also with language. According to these perspectives, human activity starts operating in the sensorial level, which takes man to the base of his perceptual experience. In order to draw this parallel, we will first address the key concepts of the Merleau-Pontyan phenomenology - the flesh, reversibility, chiasm, visible/invisible. Then we will level them to literary concepts, based on ideas of poets, writers, critics and scholars. By pointing out the similarities between phenomenology and literature, we aim to understand the latter as being a phenomenon in its essence. To sustain our argument, we shed light on the debate over child literature and particularly on the very idea of infancy. This helps deepen the previously established bonds between the fields of knowledge dealt here. Finally, under the light of phenomenology and of literature, we will look at two major literary works: the prose of Bartolomeu Campos de Queirós s The glass eye of my grandfather , and the poetry of Manoel de Barros s Ascension